Vulnerabilidad de fachadas del Centro Histórico de la ciudad de Morelia - Torres Arreola, Diana María (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
This study analyzes the seismic vulnerability of the façades in Morelia’s Historic Center, declared a UNESCO World Heritage Site, with the aim of contributing to the conservation of the built heritage. The buildings in the center present traditional construction typologies with façades that are structurally independent from the rest of the structure, a condition that increases their susceptibility to overturning failures during seismic events. Factors such as surface deterioration, including erosion, humidity, and loss of coatings, directly affect their structural stability. A total of 577 façades distributed across 27 city blocks of the Historic Center were evaluated through visual inspections, photographic surveys, and in situ measurements. Thirteen parameters were analyzed, including geometric aspects, materials, state of conservation, structural connections, and attached elements, in order to estimate vulnerability indices and average damage grades under seismic intensities equivalent to VI and IX. The results obtained allow for the characterization of the current state of conservation and vulnerability of the façades, providing a technical basis for defining intervention and reinforcement strategies. The study seeks to offer useful tools for seismic risk management in heritage areas and for the preservation of the historical and architectural value of Morelia’s Historic Center.

El presente trabajo analiza la vulnerabilidad sísmica de las fachadas del Centro Histórico de Morelia, declarado Patrimonio Mundial por la UNESCO, con el objetivo de contribuir a la conservación del patrimonio edificado. Las edificaciones del centro presentan tipologías constructivas tradicionales con fachadas independientes del resto de la estructura, condición que incrementa su susceptibilidad a fallas por volteo durante eventos sísmicos. Factores como el deterioro superficial incluyendo erosión, humedad y pérdida de recubrimientos, afectan directamente su estabilidad estructural. Se evaluaron 577 fachadas distribuidas en 27 manzanas del Centro Histórico mediante inspecciones visuales, levantamientos fotográficos y mediciones in situ. Se analizaron 13 parámetros que incluyen aspectos geométricos, materiales, estado de conservación, conexiones estructurales y elementos anexos, con el fin de estimar índices de vulnerabilidad y grados medios de daño ante intensidades sísmicas equivalentes a VI y IX. Los resultados obtenidos permiten caracterizar el estado actual de conservación y vulnerabilidad de las fachadas, ofreciendo una base técnica para definir estrategias de intervención y reforzamiento. El estudio busca aportar herramientas útiles para la gestión del riesgo sísmico en zonas patrimoniales y para la preservación del valor histórico y arquitectónico del Centro Histórico de Morelia.
Facultad de Ingeniería Civil. Maestría en Ingeniería en el área de Estructuras
Keywords: info:eu-repo/classification/cti/7; FIC-M-2025-1485; Vulnerabilidad sísmica; Conservación; Fachadas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19460